OVERCOMING THE ANTINOMIES OF HUMAN EXISTENCE: ONTOLOGY OF TRICKSTER - T. V. Danylova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. This paper aims to study the ontological status of a trickster character in “Panchatantra” and its receptions. Methodology. The author has used analytical methodology of C. Levi-Strauss, C. Jung’s theory of archetypes, and hermeneutical methodology. Theoretical basis and results. Perception of the world in the form of a narrative is inherent in the very specifics of the human thinking. Among the most famous literary narratives that structured cultural experience of different nations are the framed story “Panchatantra” and its receptions “Kalilah and Dimnah” and “Stefanit and Ihnilat”. The framework of the analyzed text is the story about two jackals Karataka and Damanaka, Lion, and Bull. “Panchatantra” is deeply rooted in the animal epos, which is based on the totemic myth. Myths were created by primitive thinking that sought to systematize the world, to give it order through binary oppositions. Their hard core is “Life – Death” opposition. A myth deals with oppositions and seeks to neutralize them. Thus, a myth serves as the logical tool to overcome the fundamental contradictions. This is carried out by introducing a mediator. Two poles, two extreme points are unambiguous; ambiguity “occurs” at an intermediate stage only. Shift from one point to another is impossible directly – for this we need a mediator. In the given narrative the binary opposition “Life – Death” is replaced by its metaphor – Bull and Lion, herbivore (metaphor for life) and carnivore (metaphor for death). These oppositions are mediated by Jackal (Karataka&Damanaka) that feeds on carrion and has a dual nature. A mediator, which overcomes or at least mitigates the binary opposition, is seen as a compromise between herbivores and carnivores that embody the antinomy of life and death. This mediator is a trickster – bipolar character (good and evil at the same time). A trickster freely acts in unordered world of Chaos without Life – Death limitations. Scientific novelty. The breaking of cyclical time of the myth and deploying it into linear time gave rise to characters-doubles: the only one mythological image disintegrated and turned into different actors. A phenomenon of events became the basis of narrative storytelling. “Panchatantra”, “Kalilah and Dimnah”, “Stefanit and Ihnilat” have a dialogical form, which can be seen as a dialogue within one personality, i.e. at a certain stage one single mediator is splitting, and we get two characters – Karataka and Damanaka, Kalilah and Dimnah, Stefanit and Ihnilat. They represent opposing views and wisely defend their positions. This dialogue-dispute has neither beginning nor end. Karataka and Damanaka are the bifurcation of one single synthetic character – the manifestation of bipolar worldview that combines the opposing principles of life. Conclusion. The true nature of a trickster opposes any restrictions: it is open to everything. A trickster is free to move from one pole to another, he constructs reality and plays with it metaphorically overcoming the antinomy of life and death.